"KÜRESELLEŞEN" DÜNYADA YETİŞKİN EĞİTİMİ - Rıfat MİSER (Ankara Üniversitesi Eğitim Bilimleri Fakültesi Dergisi)
The term "globalisation" has been one being used oftenly nowadays. The reason for this, the development of financal capital, competation, and transportation- communication- information technologies are affecting wordwide. The factors are also affecting adult education. The subject of this article is to review the effect of factors that cause globalisation on labor, employment, right for education, inter-cultural relations, and literacy in context adult education